Participatory Politics and ‘user involvement’ (Concept: The Journal of Contemporary Community Education Practice Theory, 2012)
This article considers the policy discourse of social inclusion in participatory politics and, with a particular focus on the UK welfare state, the evolution of the ‘user’ within participatory fora. A selection of typologies that aid understanding of the forces at work within the structures and spaces of participatory politics are subsequently examined. The roles and identities of those included (or excluded) in participatory processes are considered, with a particular examination of identity within the sphere of mental health. The article concludes by discussing the resultant parameters and implications for community education practice.